+0  
 
0
55
2
avatar

Can someone help complete the square?

 

4m^2 - 12m + 13 = 0 

 

thank you!

Guest Sep 2, 2017
Sort: 

2+0 Answers

 #1
avatar
0

Can someone help complete the square?

 

4m^2 - 12m + 13 = 0 

 

 

 

 

Solve for m:
4 m^2 - 12 m + 13 = 0

Divide both sides by 4:
m^2 - 3 m + 13/4 = 0

Subtract 13/4 from both sides:
m^2 - 3 m = -13/4

Add 9/4 to both sides:
m^2 - 3 m + 9/4 = -1

Write the left hand side as a square:
(m - 3/2)^2 = -1

Take the square root of both sides:
m - 3/2 = i or m - 3/2 = -i

Add 3/2 to both sides:
m = 3/2 + i or m - 3/2 = -i

Add 3/2 to both sides: 
 m = 3/2 + i          or             m = 3/2 - i

Guest Sep 2, 2017
edited by Melody  Sep 2, 2017
 #2
avatar
0

\(\displaystyle 4m^{2}-12m+13\\=4(m^{2}-3m)+13\\=4(m^{2}-3m+9/4-9/4)+13\\=4\{(m-3/2)^{2}-9/4\}+13 \\=4(m-3/2)^{2}-9+13\\=4(m-3/2)^{2}+4.\)

Guest Sep 3, 2017

8 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details